The Implementation of Tri Hita Karana in Civics Education Learning Based on the Petik Laut Madura Culture for Fifth Grade Elementary School Students - Romli, Muhammad; Lasmawan, I Wayan; Sanjaya, Dewa Bagus (Universitas Cokroaminoto Palopo, 2025)
Integration of Tri Hita Karana (THK), a Balinese philosophy emphasizing harmony between humans, God, others, and the environment, into Civics Education (PKN) is an innovative approach to character development in elementary schools. This study explores the application of THK values through the local tradition of Petik Laut Madura, focusing on its impact on students’ teamwork, social responsibility, and environmental awareness. The research aims to understand how THK and Petik Laut can enhance students' understanding of cultural identity and character building in a relevant and engaging manner. A qualitative descriptive method was employed, involving 35 fifth-grade students from SDN Parsanga II. Data collection techniques included classroom observations, interviews, and analysis of students’ projects. The findings revealed that integrating THK principles with the Petik Laut tradition significantly improved students’ collaboration and engagement in learning. Students demonstrated increased empathy, social responsibility, and a stronger connection to cultural and environmental values. This research concludes that THK-based learning, contextualized within local traditions, is effective in fostering character development and cultural awareness in students. The study highlights the potential of local wisdom as a foundation for developing civic-minded, socially responsible, and environmentally conscious young citizens.